Long‐term follow‐up after proton beam therapy for pediatric tumors: a Japanese national survey. Issue 3 (3rd April 2017) - Mizumoto, Masashi; Murayama, Shigeyuki; Akimoto, Tetsuo; Demizu, Yusuke; Fukushima, Takashi; Ishida, Yuji; Oshiro, Yoshiko; Numajiri, Haruko; Fuji, Hiroshi; Okumura, Toshiyuki; Shirato, Hiroki; Sakurai, Hideyuki
Abstract : Proton beam therapy (PBT) is a potential new alternative to treatment with photon radiotherapy that may reduce the risk of late toxicity and secondary cancer, especially for pediatric tumors. The goal of this study was to evaluate the long‐term benefits of PBT in cancer survivors. A retrospective observational study of pediatric patients who received PBT was performed at four institutions in Japan. Of 343 patients, 62 were followed up for 5 or more years. These patients included 40 males and 22 females, and had a median age of 10 years (range: 0–19 years) at the time of treatment. The irradiation dose ranged from 10.8 to 81.2 GyE (median: 50.4 GyE). The median follow‐up period was 8.1 years (5.0–31.2 years). The 5‐, 10‐ and 20‐year rates for grade 2 or higher late toxicities were 18%, 35% and 45%, respectively, and those for grade 3 or higher late toxicities were 6%, 17% and 17% respectively. Univariate analysis showed that the irradiated site (head and neck, brain) was significantly associated with late toxicities. No malignant secondary tumors occurred within the irradiated field. The 10‐ and 20‐year cumulative rates for all secondary tumors, malignant secondary tumors, and malignant nonhematologic secondary tumors were 8% and 16%, 5% and 13%, and 3% and 11%, respectively. Our data indicate that PBT has the potential to reduce the risk of late mortality and secondary malignancy. Longer follow‐up is needed to confirm the benefits of PBT for pediatric tumors. Abstract : A retrospective observational study of pediatric patients who received PBT was performed at four institutions in Japan. Of 343 patients, 62 were followed up for 5 or more years. The 5‐, 10‐ and 20‐year rates for grade 2 or higher late toxicities were 8%, 35% and 45%, respectively, and those for grade 3 or higher late toxicities were 6%, 17% and 17% respectively. The irradiated site (head and neck, brain) was significantly associated with late toxicities. No malignant secondary tumors occurred within the irradiated field. The 10‐ and 20‐year cumulative rates for all malignant secondary tumors were 5% and 13%, respectively. Our data indicate that PBT can reduce the risk of late mortality and secondary malignancy.